Fresno County Bar Associations' 105th Annual Bar Banquet - Watkins, Howard::::::::: (1987)
Herbert Levy presents Howard Watkins an Fresno County Bar Association gift of appreciation Fresno County Young Lawyers Association President Brad Hill and Judge Leonard Meyers (ret.) applauding